Histochemical characterization and connective fiber distribution of the cardiac outflow tract of pirarucu, Arapaima gigas (Schinz, 1822) (Osteoglossiformes, Arapaimidae) - Gardinal, Mario Vitor Buzete [UNESP]; Ruiz, Thalles Fernando Rocha [UNESP]; dos Santos, Diego Dias [UNESP]; Vidal, Mateus Rossetto [UNESP]; Moron, Sandro Estevan; Falleiros Junior, Luiz Roberto [UNESP]; Taboga, Sebastião Roberto [UNESP]; Franceschini Vicentini, Irene Bastos [UNESP]; Vicentini, Carlos Alberto [UNESP] (Springer Nature, 2019)
The cardiac outflow tract (OFT) in teleosts is composed of a proximal short conus arteriosus and a distal well-developed bulbus arteriosus located between the ventricle and ventral aorta. The role of these anatomical components includes structural connections, prevention of blood backflow and blood pressure control, which are related to their histological and histochemical compositions. A previous study in the heart of the Amazonian species Arapaima gigas reported an unusual OFT arrangement among teleosts that has been found only in members of Osteoglossiformes so far. Thus, considering the wide structural variability of the teleostean OFT, the present study focuses on identifying glycosaminoglycans types and describing the distribution of collagen, elastic and reticular fibers in the conus arteriosus, conal valves, and bulbus arteriosus of A. gigas. Hearts from A. gigas between 327 and 4040 g weight were used. Collagen fibers were concentrated in regions that were regularly exposed to stress, as elastic fibers showed a broad distribution in all anatomical segments. Several fibrous connections between the conal valve leaflets and the conus arteriosus were observed, possibly acting as the primary connection form. The functions of the connective fibers in the valve leaflets and the bulbus are supported by an extracellular matrix rich in non-sulfated glycosaminoglycans. The complex reticular fiber network in the compact myocardium of the conus and the smooth muscle of the bulbus wall suggests a relevant role in support contraction of both muscle types, and in attachment and mobility of the conal valve leaflets.
Keywords: Amazonian teleost; Collagen; Elastin; Heart; Reticular fibers